2002
DOI: 10.1016/s0002-9440(10)64433-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Appraisal of Thyroid Cancer Progression

Abstract: Several lines of evidence suggest that follicular cellderived thyroid cancers represent a continuum of disease that progresses from the highly curable welldifferentiated thyroid cancers to the universally fatal anaplastic cancers. However, the genetic mechanisms underlying thyroid cancer progression remain ill defined. We compared the molecular-cytogenetic profiles derived from comparative genomic hybridization (CGH) analysis of major histological variants of thyroid cancer to define genetic variables associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
118
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(132 citation statements)
references
References 46 publications
13
118
0
1
Order By: Relevance
“…Indeed, our group showed that the median number of chromosomal abnormalities per case rises from 1 in well-differentiated PTC to 10 in anaplastic carcinoma, with intermediate values of 3 and 5 for TCV and PDTC, respectively. 17 In a minority of cases, morphologic instability was best demonstrated in cases in which the metastasis demonstrated a betterdifferentiated histology compared with the primary tumor. This phenomenon has been previously reported in bone metastases from thyroid carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our group showed that the median number of chromosomal abnormalities per case rises from 1 in well-differentiated PTC to 10 in anaplastic carcinoma, with intermediate values of 3 and 5 for TCV and PDTC, respectively. 17 In a minority of cases, morphologic instability was best demonstrated in cases in which the metastasis demonstrated a betterdifferentiated histology compared with the primary tumor. This phenomenon has been previously reported in bone metastases from thyroid carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to well-differentiated carcinomas, anaplastic thyroid carcinomas are more likely to be aneuploid, 5 they demonstrate a much higher prevalence of loss of heterozygosity, 1,6 and they harbor alterations of key regulators of cell growth and differentiation that are not targeted in earlier stages of tumorigenesis. 7,8 As one example, mutations of p53 are commonly noted in anaplastic thyroid carcinomas, but they are rarely present in well-differentiated thyroid carcinomas. [9][10][11][12] BRAF encodes a serine-threonine kinase that acts in the mitogen activated protein kinase (MAPK) pathway.…”
mentioning
confidence: 99%
“…Molecular and immunohistochemical studies directed to detect specific gene profiles and related proteins in thyroid cancer have been extensively reported in literature (Bartolazzi et al, 2001;Huang et al, 2001;Ruco et al, 2001;Wreesmann et al, 2002). Experimental data, mostly arising from the molecular analysis of papillary thyroid carcinoma (PTC), contributed to identify a panel of genes overexpressed in thyroid malignancy.…”
mentioning
confidence: 99%